Advances in Polymeric In Situ Drug Delivery and Soft Biosensors: Innovations in Biochemical Sensing and Personalized Healthcare - Rakshit Sanwal (International Journal of Cheminformatics, 2024)
Advanced healthcare and personalized medicine are undergoing a transformation thanks to in situ medication delivery systems and biochemical sensor technology. Polymeric in situ drug delivery systems form gels upon administration, releasing medications in a controlled manner and providing benefits such as ease of administration and enhanced patient compliance. Similarly, advancements in soft electronics, including flexible and stretchable biosensors, enable continuous, in situ biochemical monitoring, conforming to complex biological environments like human tissue. This review explores both the formulation of in situ gel systems and the integration of soft, flexible biosensors for real-time, in situ biochemical sensing. We discuss polymers and solvents central to gel formation, methods for designing stimuli-responsive drug delivery systems, and applications of soft electronics in healthcare settings. Finally, we address manufacturing challenges, including material selection and sensor integration techniques, while considering future directions in bioelectronics and polymeric drug systems, aiming to bridge the gap between traditional therapeutic approaches and emerging bio-sensing technologies.
Keywords: Biochemical sensing; In situ drug delivery; flexible electronics; personalized healthcare; polymeric gel systems; soft biosensors